3 - Translating Equitable Access into Retention and Success in African Higher Education: The Role and Responsibility of Individual Institutions - Sabiha Y. Essack (Journal of Higher Education in Africa, 2012)
Matching equity of access to equity of outcome in marginalized groups in African higher education necessitates innovative strategies in pre- and post- student admission. Student selection using tools predictive of student success, comprehensive and holistic student support, and, curriculum and pedagogical interventions address both access and success within the equity and transformation paradigms. This article provides an overview of higher education participation rates in African countries and describes curriculum, pedagogic and student support strategies that facilitate the translation of access into retention and success.